Comparison of Three Anxiety Management Protocols for Extraction of Third Molars With the Use of Midazolam, Diazepam, and Nitrous Oxide: A Randomized Clinical Trial - Moares, Michelle Bianchi de [UNESP]; Barbier, Winnie Souza [UNESP]; Raldi, Fernando Vagner [UNESP]; Nascimento, Rodrigo Dias [UNESP]; Santos, Lucio Murilo dos [UNESP]; Loureiro Sato, Fabio Ricardo [UNESP] (Elsevier B.V., 2019)
Purpose: The objective of the present study was to compare 3 sedation protocols using diazepam, midazolam, and nitrous oxide. Patients and Methods: A total of 120 patients with an indication for extraction of third molars were selected. All 120 patients had had moderate to severe levels of anxiety according to the Corah Dental Anxiety Scale. The patients were randomly divided into 3 groups. The patients' vital signs were measured, and the results analyzed by descriptive statistical analysis and statistical tests of comparison. Results: No statistically significant differences were found in the patients' heart rate. However, the differences in the systolic and diastolic blood pressure were statistically significant after 15 minutes of nitrous oxide sedation. The oximetry data showed no differences among the 3 sedation protocols. We also found no statistically significant differences in the retrograde amnesia test. The differences in anxiety from pre-operatively to postoperatively were statistically significant for all techniques, demonstrating their effectiveness in anxiety control. Conclusions: All 3 preoperative sedation techniques for anxious patients undergoing extraction of third molars used in the present study were effective in controlling the anxiety, with little effect on the patients' vital signs and retrograde amnesia. (C) 2019 American Association of Oral and Maxillofacial Surgeons